SOCIOLOGICAL IMPACT OF VOTE BUYING IN NORTH-WEST ZONE OF NIGERIA: THE STUDY OF THE 2015 AND 2019 ELECTIONS - MU’AZU AHMED MOHAMMED (International Studies Journal)
Vote buying is a widespread phenomenon in Nigeria. It involves an exchange in which the voters sell their votes to the buyer for money during election. This phenomenon has impacted negatively in the Nigeria’s free and fair election processes. The ill competent ones occupied elective political positions because they used money to secured votes, while the qualified ones were left behind hence, they were unable to use money during primary and secondary elections. The objective of the study was to find out the impact of vote buying on electing people to various political positions in North West Zone of Nigeria. The theory of Collective Action was used in explaining the study findings. Two different but complementary methods of data collections (questionnaire and in-depth interview) were used to obtained the needed information. The findings revealed among others that; sometimes credible candidates were denied opportunity to even contest, that many of those that were able to buy their ways were not been able to perform to expectations, etc. The study recommended among others; that more political awareness against vote buying should be put in place, that laws prohibiting votes buying should be implemented accordingly etc.